2012
DOI: 10.1021/jf204848b
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Versatile Antioxidant Mechanisms of Action of Rosmarinate Alkyl Esters in Oil-in-Water Emulsions

Abstract: The antioxidant polar paradox postulates that nonpolar antioxidants are more effective in oil-in-water emulsions than polar antioxidants. However, this trend is often not observed with antioxidants esterified with acyl chains to vary their polarity. In this study, the nonpolar eicosyl rosmarinate (20 carbons, R20) was less effective at inhibiting lipid oxidation in oil-in-water emulsions than esters with shorter fatty acyl chains such as butyl (R4), octyl (R8), and dodecyl (R12) esters. Interestingly, in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
123
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 126 publications
(139 citation statements)
references
References 26 publications
15
123
1
Order By: Relevance
“…In particular, this is the case in oil-in-water emulsions when an excess of surfactant is added (more than is needed to saturate the emulsion droplet surface). Using rosmarinate alkyl esters in a stripped soybean oil-in-water emulsion, it has been shown that eicosyl rosmarinate (20 carbon atoms) is mainly located in the oil droplet, whereas butyl and dodecyl rosmarinates are predominantly concentrated at the interface (Panya et al 2012). As expected, a cut-off effect was observed: butyl and dodecyl rosmarinates were much better antioxidants than was eicosyl rosmarinate ester.…”
Section: Unlocking the Antioxidant Mass Transport Mechanism To Undersmentioning
confidence: 52%
See 3 more Smart Citations
“…In particular, this is the case in oil-in-water emulsions when an excess of surfactant is added (more than is needed to saturate the emulsion droplet surface). Using rosmarinate alkyl esters in a stripped soybean oil-in-water emulsion, it has been shown that eicosyl rosmarinate (20 carbon atoms) is mainly located in the oil droplet, whereas butyl and dodecyl rosmarinates are predominantly concentrated at the interface (Panya et al 2012). As expected, a cut-off effect was observed: butyl and dodecyl rosmarinates were much better antioxidants than was eicosyl rosmarinate ester.…”
Section: Unlocking the Antioxidant Mass Transport Mechanism To Undersmentioning
confidence: 52%
“…Twenty-eight formulations were associated with an estimated proportion of unadsorbed emulsifiers higher than 90%; 20 resulted in an unadsorbed proportion of 70-90%, and 13 in an unadsorbed proportion of 50-70%. There is abundant experimental evidence from studies using oil-in-water emulsions and microemulsions that unadsorbed surfactants present in the aqueous phase at concentrations higher than their critical micelle concentration (CMC) serve as vehicles for transferring antioxidants (Kiralan et al 2014;Laguerre et al 2009Laguerre et al , 2010Panya et al 2012;Richards et al 2002), hydroperoxides (Nuchi et al 2002), and iron (Cho et al 2002) from the oily phase to the aqueous one and/or the interface.…”
Section: Mass Transfer Phenomena In Lipid Dispersions: a Working Hypomentioning
confidence: 99%
See 2 more Smart Citations
“…Although this has proven to be a simplification (Panya et al, 2012), it does illustrate the important effect of product (micro)structure on the oxidation process and the efficiency of antioxidants used in different systems.…”
Section: Novel Approaches For the Prevention Of Oxidationmentioning
confidence: 99%